Design of parallel and pipelined DA based OBC fir filter for software defined radio - Rajmohan Madasamy; Himanshu Shekhar (Institute of Advanced Engineering and Science, 2019)
Software Defined Radio (SDR) is a new technology used to implement different wireless communication standard for mobile communication. The Intermediate Frequency (IF) block is the most demanding block in software defined radio. The most important task in intermediate processing block is digital filtering which is carried out by Finite Impulse Response (FIR) filter. One of the major techniques for the calculation of inner product is Distributed Arithmetic (DA) based FIR filter which uses Look Up Table (LUT) to eliminate the need of multiplier. The efficiency of the DA filter is affected with the increasing number of address line and also due to its serial operation. To overcome this problem parallel and pipeline based DA filter using Offset Binary Coding (OBC) for Two Bit At A Time (2-BAAT) is proposed. Our proposed method achieves less area, low power consumption and nominal delay for SDR application.